2020
DOI: 10.1172/jci135439
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA H19X is a key mediator of TGF-β–driven fibrosis

Abstract: Chimique Belge (UCB) in the area of potential treatments for scleroderma and its complications. In addition, OD has a patent on mir-29 for the treatment of systemic sclerosis issued (US8247389, EP2331143).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 56 publications
4
44
0
Order By: Relevance
“…22 The RNA-seq-derived lincRNA MIR503HG is located at chromosome X, and harbors a coding sequence of miR-503 that is embedded in the first intron. 5,23 MiR-503 is overexpressed in various types of diabetes, especially in complications related to diabetes. MiR-503 was involved in the protective effect of Phase II enzyme inducer (CPDT) in diabetic cardiomyopathy via Nrf2/ARE signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 The RNA-seq-derived lincRNA MIR503HG is located at chromosome X, and harbors a coding sequence of miR-503 that is embedded in the first intron. 5,23 MiR-503 is overexpressed in various types of diabetes, especially in complications related to diabetes. MiR-503 was involved in the protective effect of Phase II enzyme inducer (CPDT) in diabetic cardiomyopathy via Nrf2/ARE signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…MIR503HG, also known as H19X is an intergenic lncRNA and its gene locus encodes two microRNAs (miR-503, miR-424). And miR-503 is embedded in the first intron; 5 therefore miR-503 is an intronic microRNA. In hepatocellular carcinoma (HCC) cell lines, the expression levels of miR-335 were significantly correlated with those of its protein-coding host gene, MEST , supporting the notion that the intronic miR-335 was co-expressed with its host gene under the control of host gene promoter.…”
Section: Introductionmentioning
confidence: 99%
“…lncRNAs are being extensively studied owing to their vast potential as drug targets for immunological diseases, cardiovascular diseases, and cancers (Atianand & Fitzgerald, 2016). Since H19X is a placenta-specific lncRNA that plays critical roles in trophoblasts, it could be a viable target for placenta-related disease (Pachera et al , 2020; Yu et al , 2018). Elucidating the mechanism underlying the actions of H19X and PIWIL1 could pave the way for the development of treatments for placenta-related disease in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…X inactivate-specific transcript (XIST) could facilitate EMT induced by TGF-β through miR-367/141-ZEB2 axis in NSCLC [ 82 ]. Furthermore, studies of Pachera et al showed lncRNA H19X, which was served as a critical regulator of TGF-β–driven tissue fibrosis, could be induced by TGF-β in a time- and dose-dependent manners in fibroblasts [ 83 ]. Similarly, in HCC TGF-β and lncRNAs could be able to influence each other through diverse mechanisms, which have been reported in HCC initiation and progression.…”
Section: The Interaction Of Tgf-β and Lncrnas In Hcc: How They Influementioning
confidence: 99%